2015
DOI: 10.3109/08916934.2015.1030616
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a induces apoptosis via increasing the Bax:Bcl-2 ratio in dermal fibroblasts of patients with systemic sclerosis

Abstract: The most prominent feature of systemic sclerosis (SSc) and other diseases associated with fibrosis is the prolonged activation of fibroblasts not eliminated by apoptosis, hence characterized by accumulation of more extra cellular matrix (ECM). We tend to verify if microRNA-29a (miR-29a) as an anti-fibrotic factor could induce apoptosis in SSc fibroblasts. We did not detect apoptosis in SSc fibroblasts. We found that Bcl-2 expression was upregulated in SSc fibroblasts and the ratio of Bax:Bcl-2 in these cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 55 publications
5
35
0
Order By: Relevance
“…High fibrogenic activity in cell cultures after miR-29a knockdown also extrapolated the existence of abundant fibrotic matrices in synovial compartment in end-stage OA. Our analyses agreed with other studies demonstrating that the miR-29 family reduces TGF-β1 signaling exaggeration of fibrotic matrix deposition in fibroblast cultures from cardiac 33 , lung 34 , and systemic sclerotic tissues 35 . Current investigations indicated that miR-29a signaling exerted a protective function against excessive synovial remodeling.…”
Section: Discussionsupporting
confidence: 92%
“…High fibrogenic activity in cell cultures after miR-29a knockdown also extrapolated the existence of abundant fibrotic matrices in synovial compartment in end-stage OA. Our analyses agreed with other studies demonstrating that the miR-29 family reduces TGF-β1 signaling exaggeration of fibrotic matrix deposition in fibroblast cultures from cardiac 33 , lung 34 , and systemic sclerotic tissues 35 . Current investigations indicated that miR-29a signaling exerted a protective function against excessive synovial remodeling.…”
Section: Discussionsupporting
confidence: 92%
“…reported similar results obtained in a TUNEL (TdT‐mediated dUTP nick‐end labeling) assay . Our recent study represented the first report to suggest that an miRNA (i.e. miR‐29a) restoration induces apoptosis in SSc fibroblasts.…”
Section: Discussionsupporting
confidence: 78%
“…Proteins involved in cell cycle regulation, CCND1 and CDK2/4, were all reduced after the siTRPM7 treatment. Moreover, proteins involved in apoptosis were strongly altered, especially imbalance of the BAX/BCL2 ratio, which is involved in mitochondrial-dependent apoptosis [62, 63], and related proteins including cleaved-caspase 3 [64, 65] and Cytochrome C [66, 67], suggesting that TRPM7 deficiency could trigger a mitochondrial-mediated apoptosis. Importantly, as suggested by our microarray analysis, MAPK signaling pathway, a central regulator in the pathway network, could be altered by the affected calcium signaling pathway due to TRPM7 knockdown.…”
Section: Discussionmentioning
confidence: 99%